ANALISIS KOMPETENSI SUMBER DAYA MANUSIA PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA BOGOR - Olisah, Olisah; Hernawan, Denny; Purnamasari, Irma (Jurnal Governansi, 2019)
The aim of this research is to describe the competency of human resources, namely civil servants, and the obstacles faced by the Local Office of Public Work and Spatial Planning in Bogor City. The theory of this research stems from Spencer and Spencer’s theory on competency, including five dimensions, namely knowledge, skill, trait, self-concept, and motive. The method of this research is descriptive method. The samples of this research determine 54 respondents from 117 civil servants. The data of this research is collected by using the field research (observation, interview, and questionnaire) to collect primary data and the library research to collect secondary data. The data of questionnaires is analyzed by using the Weight Mean Score formula to count the mean score. The secondary data is used to enrich the discussion of this research. The result of this research indicate the mean score of civil servant competency 4.25 included in best criteria. It means that a majority of civil servants has good competency to conduct the main task and function in order to achieve the goals of the local office. Moreover, there are still some civil servants who have not competencies, as indicated in the lack of skill certificate, formal education, and training. Keywords: Competency, Human Resource, Civil Servant.